2007
DOI: 10.1177/0363546507299745
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of High School and Collegiate Football Injuries in the United States, 2005-2006

Abstract: Patterns of football injuries vary, especially by type of exposure and level of play. Future studies should continue to compare differences in injury patterns in high school and collegiate football, with particular emphasis placed on high-risk plays (running plays) and positions (running backs and linebackers).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
247
5
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(266 citation statements)
references
References 19 publications
13
247
5
1
Order By: Relevance
“…5 Knee injuries have also been reported to represent the second and third largest proportions of injuries in high school and collegiate football players, respectively. 6 Ankle injuries constituted the highest proportion of injuries in high school and collegiate football players. 6 Injuries to the head and face have been responsible for the fifth and sixth largest proportions of injuries in high school and collegiate football players, respectively.…”
mentioning
confidence: 99%
“…5 Knee injuries have also been reported to represent the second and third largest proportions of injuries in high school and collegiate football players, respectively. 6 Ankle injuries constituted the highest proportion of injuries in high school and collegiate football players. 6 Injuries to the head and face have been responsible for the fifth and sixth largest proportions of injuries in high school and collegiate football players, respectively.…”
mentioning
confidence: 99%
“…Therefore, the fact that the number of collisions is similar between the USA and Japan, despite the shorter matches in Japan, indicates that the actual number of collisions is higher among Japanese university players compared to players in the USA. In the USA, many studies are in agreement with the fact that the injury rate during games is higher than that during practice sessions 1,2,4) , and have reported that the number of collisions during a game is 2-3 times higher than that during a practice session 10,12) . However, in this study, the number of collisions during practice sessions was only 1.3 times higher than that in games.…”
Section: Discussionmentioning
confidence: 65%
“…Currently, American players receive stronger head collisions than Japanese players, but it was revealed that in both countries, players receive head collisions of with an average of 20 g, both during practice sessions and games. Another common factor is that the impact of head collisions during a game is significantly higher than during a practice session, which would mean that the injury rate would be higher as well during games than during practices 1,2,4) ; this indicates the effect of the collision impact magnitude. However, data on Japanese university players are limited, and further data collection should be done before comparing them with their American counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 A Joint Commission of the American Academy of Neurology, American Neurology Society, and Child Neurology Society report describes an ethical obligation to protect the athletes' current and future physical and mental health while informing athletes, parents, and medical professionals about the risks of concussion and postconcussive impairments. 3 Although some agreement exists, diagnosis and management of concussion are continually evolving as new data become available. 4 The International Conference on Concussion in Sport and an elevated level of media attention 5 in recent years have spurred sports medicine clinicians to standardize diagnosis, management, and reporting guidelines for athletes sustaining traumatic brain injury during athletic competition.…”
Section: Introductionmentioning
confidence: 99%